Impact of Bromocriptine-QR Therapy on Glycemic Control and Daily Insulin Requirement in Type 2 Diabetes Mellitus Subjects Whose Dysglycemia Is Poorly Controlled on High-Dose Insulin: A Pilot Study - Erin D. Roe; Bindu Chamarthi; Philip Raskin (Journal of Diabetes Research)
Background. The concurrent use of a postprandial insulin sensitizing agent, such as bromocriptine-QR, a quick release formulation of bromocriptine, a dopamine D2 receptor agonist, may offer a strategy to improve glycemic control and limit/reduce insulin requirement in type 2 diabetes (T2DM) patients on high-dose insulin. This open label pilot study evaluated this potential utility of bromocriptine-QR. Methods. Ten T2DM subjects on metformin (1-2 gm/day) and high-dose (TDID ≥ 65 U/day) basal-bolus insulin were enrolled to receive once daily (morning) bromocriptine-QR (1.6–4.8 mg/day) for 24 weeks. Subjects with at least one postbaseline HbA1c measurement (N=8) were analyzed for change from baseline HbA1c, TDID, and postprandial glucose area under the curve of a four-hour mixed meal tolerance test (MMTT). Results. Compared to the baseline, average HbA1c decreased 1.76% (9.74±0.56 to 7.98±0.36, P=0.01), average TDID decreased 27% (199±33 to 147±31, P=0.009), and MMTT AUC60–240 decreased 32% (P=0.04) over the treatment period. The decline in HbA1c and TDID was observed at 8 weeks and sustained over the remaining 16-week study duration. Conclusion. In this study, bromocriptine-QR therapy improved glycemic control and meal tolerance while reducing insulin requirement in T2DM subjects poorly controlled on high-dose insulin therapy.